Reinforcing Domestic Violence Prevention: The Role of Mu‘āsyarah bil-Ma‘rūf in Indonesian Legal Reform - Lisnawati, Lisnawati (UIN Sunan Kalijaga, 2023)
Domestic violence is an increasingly troubling issue, in the period 2013-2018 the trend continues to increase. Even though it has been regulated in Law Number 23 of 2004 on the Elimination of Domestic Violence, it has not been able to be overcome optimally. This article offers the integration of the principle of mu‘āsyarah bil-ma‘rūf with the articles in Law on the Elimination of Domestic Violence as an alternative to suppress the rampant of domestic violence. This research is normative legal research, using documentative data collection method, and presented by descriptive deductive-inductive method. While the approach used in this research are fiqh approach and legal approach. The results of this study show that the mu‘āsyarah bil-ma‘rūf principle is the principle of social life in a household with relationships that are appropriate and good according to Islamic law, common sense, and practiced by people in general. Between this principle and the articles of Law on the Elimination of Domestic Violence integrated in one unit of same fundamental value. The law has values of prohibition on all forms of violence. The same applies to the principle of mu'āsyarah bil-ma'rūf which contains prohibition on acts of violence that are injustice and inconsistent with the ma'rūf term. Therefore, obeying the provisions in Law on the Elimination of Domestic Violence means also obeying the rules of religion, especially for muslims as the majority in Indonesia. Kekerasan dalam rumah tangga merupakan permasalahan yang kian meresahkan, dalam kurun waktu 2013-2018 trennya terus mengalami peningkatan. Meskipun telah diatur dalam Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan dalam Rumah Tangga, namun belum dapat teratasi secara optimal. Penulis menawarkan integrasi prinsip mu‘āsyarah bil-ma‘rūf dengan pasal-pasal UU PKDRT sebagai alternatif untuk menekan maraknya KDRT tersebut. Penelitian ini merupakan penelitian hukum normatif, dengan menggunakan metode pengumpulan data dokumentatif, dan disajikan dengan metode deskriptif deduktif-induktif. Sedangkan pendekatannya menggunakan pendekatan fikih dan pendekatan hukum. Hasil penelitian ini menunjukkan bahwa prinsip mu‘āsyarah bil-ma‘rūf merupakan prinsip pergaulan hidup dalam rumah tangga dengan pergaulan yang patut dan baik menurut syari’at Islam, akal sehat, dan yang dipraktikkan orang pada umumnya. Antara prinsip ini dengan pasal-pasal UU PKDRT berintegrasi dalam satu kesatuan nilai fundamental yang sama. UU tersebut memiliki nilai pelarangan atas segala bentuk kekerasan. Begitu juga dengan prinsip mu‘āsyarah bil-ma‘rūf yang mengandung larangan atas tindakan kekerasan yang merupakan kezaliman dan tidak sejalan dengan ke-ma‘rūf-an. Dengan demikian, menaati ketentuan dalam UU PKDRT berarti juga menaati aturan agama, khususnya bagi umat Islam sebagai umat mayoritas di Indonesia.